Laser operated elasto-optical features of La 2CaB 10O 19:Pr 3+ polymer nanocomposites - Majchrowski, Andrzej A; Lakshminarayana, Gandham; Ali Hussain, Reshak, Prof. Dr.; Michalski, Edward A.; Olifierczuk, Marek; Oźga, Katarzyna; Jaroszewicz, Leszek R.; Lukasiewicz, Tadeusz; Szota, Michał; Nabialek, Marcin (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/